INTEGRATION OF ISLAMIC VALUES AND TECHNOLOGY IN BASIC EDUCATION - Nufus, Dita Durotun; Rizqi, Fatimah Tur; Syarifudin, Encep (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2025)
The rapid development of technology brings significant changes in education, including in Islamic Religious Education at the primary level. The integration of technology in Islamic Education learning offers benefits such as interactive methods and wide access to information. However, the main challenge that arises is how to optimally utilise technology without neglecting Islamic values, avoiding misuse, and maintaining a balance between technological advancement and Islamic moral principles. This research aims to explore optimal strategies in integrating technology with Islamic values in basic education. The main focus is to understand the readiness of educators and learners in utilising Islamic-based technology, as well as how the curriculum can accommodate the synergy between technology and Islamic moral education. This research uses a qualitative approach with a literature study method. Various literatures were analysed, including commentaries, scientific journals, and primary sources such as the Qur'an and Hadith. The research also reviewed best practices in the application of technology in Islamic educational institutions. Data were collected from various academic sources that discuss the integration of technology in Islamic education, as well as the results of analyses of digital-based teaching policies and practices in Islamic primary schools. The results show that technology can be an effective tool in Islamic education learning if used wisely and in accordance with Islamic principles. Educator supervision, the use of Islamic interactive applications, and a curriculum that supports Islamic values are the main factors for the success of this integration. With a balanced approach, technology can increase the effectiveness of learning without shifting the main goal of Islamic Education, which is the formation of Islamic character and morals.